Komposisi kimia kupang merah (Musculista senhausia) segar dan rebus - Nurjanah .; Agoes M. Jacoeb; Reza Nurul Ulma; Shinta Puspitasari; Taufik Hidayat (Depik, 2014)
The purpose of this study was to determine aniani4d the yield, chemical compositions, amino acids, minerals, and heavy metal residues (Pb, Hg) of fresh and boiled mussel. Amino acid was analyzed usingHPLC, minerals and heavy metals were examined using AAS and phosphorus by spectrophotometer, fatty acids by GC, and cholesterol by Liebermann-Buchard. The results showed that the chemical composition of water content, ash, protein and lipid of mussels meat were decreased about 6.09%, 2.25%, 1.39%, 0.42%, respectively after boiled while carbohydrate was increased 4.07% and the amino acids were decreased after boiling. The Ca, Mg, K, P, Na, Cu were declined after boiled, while Co, Fe, Mn and Zn were incraseed. In addition, the Pb was decreased after boiled while Hg and Se were not detected in both fresh and boiled mussel meat. SAFA fatty acids was 38.71% (fresh) and 37.31% (boiled), MUFA 8.13% (fresh) and 8.02% (boiled), PUFA 10.31% (fresh) and 8.77% (boiled), and the cholesterol contents were 102.57 mg/100 g of fresh and 100.97mg/100 g for boiled mussel meat.